(untitled) (TEL Tempo, Espaço e Linguagem, 2021)
This article seeks to analyze the contributions of the Tondal’s Vision to the construction of the medieval iconography of Christian Hell. Therefore, we will analyze the illuminures present in the Burgundian manuscript Les Visions Du Chevalier Tondal (15th century) together with the Portuguese textual version Visão de Túndalo (15th century), aiming to broaden our understanding of the reception of the Vision by the iconography of the time. Keywords: Images. Christian hell. Medieval. Tondal’s Vision.